2015
DOI: 10.1371/journal.pone.0131991
|View full text |Cite
|
Sign up to set email alerts
|

The Goblet Cell Protein Clca1 (Alias mClca3 or Gob-5) Is Not Required for Intestinal Mucus Synthesis, Structure and Barrier Function in Naive or DSS-Challenged Mice

Abstract: The secreted, goblet cell-derived protein Clca1 (chloride channel regulator, calcium-activated-1) has been linked to diseases with mucus overproduction, including asthma and cystic fibrosis. In the intestine Clca1 is found in the mucus with an abundance and expression pattern similar to Muc2, the major structural mucus component. We hypothesized that Clca1 is required for the synthesis, structure or barrier function of intestinal mucus and therefore compared wild type and Clca1-deficient mice under naive and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 81 publications
3
31
2
Order By: Relevance
“…While we observed no significant differences in Ki67+ proliferating cells in any of our models, loss of Bcl-g was linked to decreased Clca1, which is also decreased in CRC patients and is associated with inhibition of CRC epithelial differentiation when knocked down in cell lines [37,54]. Similar to Bcl-g −/− mice, Clca1 −/− mice display no overt phenotype in the acute DSS model, although mucous composition is not associated specifically with Clca1 expression [37,54]. Alternatively, changes in the mucin network in Bcl-g −/− mice may reflect changes in goblet cell restitution, a process that is not well understood.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…While we observed no significant differences in Ki67+ proliferating cells in any of our models, loss of Bcl-g was linked to decreased Clca1, which is also decreased in CRC patients and is associated with inhibition of CRC epithelial differentiation when knocked down in cell lines [37,54]. Similar to Bcl-g −/− mice, Clca1 −/− mice display no overt phenotype in the acute DSS model, although mucous composition is not associated specifically with Clca1 expression [37,54]. Alternatively, changes in the mucin network in Bcl-g −/− mice may reflect changes in goblet cell restitution, a process that is not well understood.…”
Section: Discussioncontrasting
confidence: 69%
“…We believe that the contribution of Bcl-G to the mucin network is a reflection of a potential difference in the transition from proliferation to differentiation of colonic epithelial cells. While we observed no significant differences in Ki67+ proliferating cells in any of our models, loss of Bcl-g was linked to decreased Clca1, which is also decreased in CRC patients and is associated with inhibition of CRC epithelial differentiation when knocked down in cell lines [37,54]. Similar to Bcl-g −/− mice, Clca1 −/− mice display no overt phenotype in the acute DSS model, although mucous composition is not associated specifically with Clca1 expression [37,54].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…We chose the dextran sodium sulfate (DSS) challenge model which is commonly used to study early immune reactions in mouse intestine [ 9 ]. In a previous DSS colitis study, we failed to observe any effects of Clca1-deficiency on mucus barrier integrity and mucin gene expression [ 10 ] which likely would have affected secondary immune responses. Additionally, recent studies have indicated that CLCA1 does not play a role in calcium-activated chloride secretion in the respiratory tract nor does restoration of reduced Clca1 expression rectify the cystic fibrosis electrophysiology defect in the intestine [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 88%
“…The originally confusing nomenclature of murine CLCA1, previously termed mCLCA3 or goblet cell protein-5 (gob-5), was harmonized with respect to the human and rat nomenclature in accordance with the Human Gene Nomenclature Committee and the Rat Genome Database (Erickson et al 2015). The soluble heterodimer consists of two posttranslational cleavage products, a 75 kDa amino- and a 35 kDa carboxy-terminal protein, that are processed and glycosylated from a primary 125 kDa translation product (Mundhenk et al 2006).…”
Section: Introductionmentioning
confidence: 99%